Investigating Factors Influencing Tourists' Visit Intentions - Norshamsinar, Shamsudin (2012)
The objective of this study is to investigate the relationship among factors such as Attitude, Subjective Norms, Perceived Behavioural Control, Perceived Quality and Satisfaction with Tourists’ Visit Intention. A total 132 respondents participated in this study. All five factors were found to have a positive relationship with Tourists’ Visit Intention. The Pearson correlation analysis conducted showed that Perceived Behavioural Control is the strongest factor influencing Tourists’ Visit Intention.The other four factors showed a weak relationship with Tourists’ Visit Intention.Apart from Perceived Behavioural Control, one demographic factor which is Preferred Tourists’ Destination showed a significant relationship with Tourists’ Visit Intention.Intention can explain how an action was understood and remembered, how it was responded to, and ability to predict about the future action might be taken place. Therefore,hotel operators should make an assessment of the market segment and study the abilities of their customers and try to synchronize their services to this market.